Cellularly active N-hydroxyurea FEN1 inhibitors block substrate entry to the active site - Exell, Jack C; Thompson, Mark J; Finger, L David; Shaw, Steven J; Debreczeni, Judit; Ward, Thomas A; McWhirter, Claire; Siöberg, Catrine L B; Molina, Daniel Martinez; Abbott, W Mark; Jones, Clifford D; Nissink, J Willem M; et al. (Nature chemical biology, 2016)
Structural, enzymatic and cellular target engagement studies reveal the mechanism of action by N -hydroxyurea small molecule inhibitors of the DNA repair enzyme, human flap endonuclease-1 (FEN1) that prevent cleavage of DNA flaps in cancer cells. The structure-specific nuclease human flap endonuclease-1 (hFEN1) plays a key role in DNA replication and repair and may be of interest as an oncology target. We present the crystal structure of inhibitor-bound hFEN1, which shows a cyclic N -hydroxyurea bound in the active site coordinated to two magnesium ions. Three such compounds had similar IC 50 values but differed subtly in mode of action. One had comparable affinity for protein and protein–substrate complex and prevented reaction by binding to active site catalytic metal ions, blocking the necessary unpairing of substrate DNA. Other compounds were more competitive with substrate. Cellular thermal shift data showed that both inhibitor types engaged with hFEN1 in cells, and activation of the DNA damage response was evident upon treatment with inhibitors. However, cellular EC 50 values were significantly higher than in vitro inhibition constants, and the implications of this for exploitation of hFEN1 as a drug target are discussed.